Effects of N-acetyl-l-cysteine, in vivo, against pathological changes induced by malathion. (May 2014) - Lasram, Mohamed Montassar; Bini Douib, Ines; Bouzid, Kahna; Annabi, Alya; EL ELJ, Naziha; Dhouib, Hanene; El Fazaa, Saloua; Abdelmoula, Jaouida; Gharbi, Najoua
Abstract Malathion toxicity has been related to the inhibition of acetylcholinesterase, induction of oxidative stress, liver damage and impairment of kidney function as well as hematotoxicity. N-acetyl-l-cysteine (NAC) has been shown to possess curative effects in experimental and clinical investigations. The present study was designed to evaluate the protective effect of NAC against toxic consequences of malathion exposure in Wistar rats. Malathion was given daily to rats via oral gavage and NAC in drinking water during seven days. When malathion-treated rats were compared with control, a leukocytosis and reduced hemoglobin (HGB) content were detected. Furthermore, malathion produced a significant increase in liver enzymes such as alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, lactate dehydrogenase and creatinine kinase. In addition, a decrease in acid phosphatase activity, protein and globulin levels were observed in malathion-treated rats compared with control. Moreover, analyses of the mineral status showed a disturbance in calcium, magnesium, phosphore and iron contents of the malathion-treated rats. Interestingly, NAC showed therapeutic effects against malathion toxicity. Indeed, HGB content and all liver enzymes were restored to normal values. Finally, the use of NAC as therapeutic agent for only seven days during malathion exposure showed interesting results on tissues damages.